2023
DOI: 10.1039/d3ob00437f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-iodovinyl sulfonesviadirect photoinitiated difunctionalization of internal alkynes

Abstract: Direct iodosulfonylation of internal alkynes with sulfonyl iodides, photoinitiated by violet LED light, proceeds under mild conditions, transition metals and photocatalyst free. Reaction has good functional group tolerance and high product yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…[420,421] Cascade cyclization of 1,6-enynes triggered by the sulfonyl radical formation efficiently produced functionalized pyrrolidine derivatives in good to excellent yields (Scheme 62). [422] In all cases, high tolerance to the side functional groups were demonstrated, including halogenated alkyl groups [414,420,421] or aromatic rings, [413,[415][416][417][418][419]422] nitrile, [413] ester, [413,419] nitro, [413,419] acetamide, [413] or strained saturated (hetero)cycles. [413,419]…”
Section: Chemoselective Reactions Of Other Functionalized Sulfonyl Ha...mentioning
confidence: 98%
See 1 more Smart Citation
“…[420,421] Cascade cyclization of 1,6-enynes triggered by the sulfonyl radical formation efficiently produced functionalized pyrrolidine derivatives in good to excellent yields (Scheme 62). [422] In all cases, high tolerance to the side functional groups were demonstrated, including halogenated alkyl groups [414,420,421] or aromatic rings, [413,[415][416][417][418][419]422] nitrile, [413] ester, [413,419] nitro, [413,419] acetamide, [413] or strained saturated (hetero)cycles. [413,419]…”
Section: Chemoselective Reactions Of Other Functionalized Sulfonyl Ha...mentioning
confidence: 98%
“…[411] This knowledge was used to develop a series of atom transfer radical addition (ATRA)type [412] reactions, e.g., recently published addition of sulfonyl bromides and iodides to [1.1.1]propellane [413] or [3.1.1]propellane (Scheme 59). [414] Radical additions to cyclopropenes in aqueous media, [415] disubstituted triple bonds under light irradiation, [416,417] and triple [418] or allenic double [419] bond in presence of a Cu(I) catalyst were also fruitful (Scheme 60).…”
Section: Chemoselective Reactions Of Other Functionalized Sulfonyl Ha...mentioning
confidence: 99%
“…42 Zhang et al reported the violet (400 nm) light-induced synthesis of (E)-β-phenoxyvinylsulfones via an EDA complex-mediated radical reaction. 43 Using visible light, we, 44 Mutra et al, 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio-and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 94%
“…Using visible light, we, 44 Mutra et al , 45 and Gurawa et al 46 have recently shown that the photoinduced addition of RSO 2 I to internal alkynes in acetonitrile occurs with high yields and regio- and stereoselectivity. Such a reaction would represent in principle an ideal atom-saving process.…”
Section: Introductionmentioning
confidence: 95%
“…In 1971, Truce and Wolf 40 exploited p -tolylsulfonyl iodide 6 as a sulfonyl and iodide source in vicinal iodosulfonylation of terminal alkynes 1 and diphenylacetylene under visible-light irradiation using a 250-W heat lamp or a 200-W medium-pressure lamp to furnish the corresponding products in 16–87% yields. In 2023, Asachenko and co-workers 41 demonstrated the direct 1,2-iodosulfonylation of internal alkynes 1 with sulfonyl iodides 6 under visible-light irradiation at room temperature in acetonitrile to give the desired β-iodovinyl sulfones 3 (Scheme 22). Photoinitiated iodosulfonylation of various symmetrical internal alkynes using p -tolylsulfonyl iodide was achieved under optimized conditions to afford the corresponding products in high yields.…”
Section: Synthesis Of β-Iodovinyl Sulfonesmentioning
confidence: 99%